Spirulina - a potential feed additive for the development of proteolytic enzymes and growth of the tropical sport fish Malaysian Mahseer (KELAH, Tor tambroides) FRY - Khan Chowdhury, Ahmed Jalal; Ambak, Mohd Azmi; Bolong, Abol-Munafi Ambok; Saad, Che Roos; Yunus, Kamaruzzaman; Alam, Md. Zahangir (2010)
Tor tambroides fry with a mean of 8.0 mm standard length (SL) and weighing (W) 0.06 g werer stocked at the rate of fifty (50) individuals in each of the fifteen 150 l rectangular fibre glass tanks for a period of 5 weeks. The development of proteolytic enzymes (Trypsin and Chymotrypsin) and growth were studied during these feeding treatments. 45% protein diet without additives was treated as control diet. The gut of the fish fry fed on control diet incorporated with 0.10% Spirulina, 0.10% enzyme, and 0.10% vitamin additives were examined. Fish fry fed on diet with 0.10% Spirulina showed significantly higher enzymatic activity (P<0.05) and growth compared to enzyme, vitamin and control diet throughout the experiment. Control diet without any additive showed lower activity than those of diets with additives. The study indicates that the incorporation of 0.10% Spirulina to a diet could be a vital factor to activate the proteolytic enzymes such as trypsin and chymotrypsin of Tor tambroides fry. The study indicates a new approach to produce low cost and nutritionally well balanced feed for Aquaculture.